Optimización del proceso de deshidratación del crudo en la planta de tratamiento del complejo de producción y facilidades Indillana (CPF) de Petroamazonas EP, bloque 15 en el año 2015. Rediseño del proceso de deshidratación del crudo en el año 2015. - Falcón Gutiérrez, Diego Patricio (2017)
Separation of crude oil phases is a major factor in crude oil production since specifications for transportation and export must be gone into effect; due to ministerial agreements and laws are executed these specifications, depending on the pipeline for which it will be transported. In the case of block 15, the Basic Sediment and Water (BSW) should be less than 0.5% because the crude oil is transported by the "Oleoducto de Crudos Pesados" (OCP). The CPF's crude treatment plant works to the limit, so it is feasible to perform the process optimization, so this research is focused on the water - crude oil separation process. A study of the equipment of the treatment plant involved in the separation of crude oil was fulfilled, which determined that the equipment, electrostatic dehydrators, does not work in a correct way according to its designs. An experimental analysis of the separation was performed that found the relationship between the variables for efficient dehydration, focusing the study on inefficient equipment. Determines the current residence time is 41.6 minutes and the residence time with the new proposal would be 69.8 minutes, achieving a better separation and a more laminar flow, which favors the process. The redesign of the separation system is proposed according to the experimental and calculation results obtained; this proposal demonstrates a financial recovery of less than one day.